The landscape of ancient mobile pastoralism in the highlands of southeastern Uzbekistan, 2000 b.c.–a.d. 1400. (August 2014) - Frachetti, Michael D.; Maksudov, Farhod
Abstract : Here we present the results of archaeological survey and excavations carried out in southeastern Uzbekistan during the summer of 2011. The sites are among the first systematically recovered pastoralist settlements in the mountains of Uzbekistan. Our data include material culture and chronology that document mobile pastoralist communities in the mountains of southern Central Asia at least as early as the middle of the 2nd millenniumb.c. Based on AMS/ 14 C chronology, detailed site stratigraphies, and evident reuse of numerous settlement sites within our dataset, we discuss the long-term land use and ecology of pastoralists in this region and argue that a well-developed local tradition of pastoralism was already in place during the early 2nd millenniumb.c. and endured until the early 20th century. Our findings reveal striking similarities with nomadic camps found elsewhere in the mountains of Inner Asia and illustrate the local durability of pastoralist landscapes during prehistoric and historical periods.